Brain-derived neurotrophic factor interacts with adult-born immature cells in the dentate gyrus during consolidation of overlapping memories - Bekinschtein, Pedro Alejandro (2014)
Successful memory involves not only remembering information over time but also keeping memories distinct and less confusable. The computational process for making representations of similar input patterns more distinct from each other has been referred to as “pattern separation.” Although adult-born immature neurons have been implicated in this memory feature, the precise role of these neurons and associated molecules in the processing of overlapping memories is unknown. Recently, we found that brain-derived neurotrophic factor (BDNF) in the dentate gyrus is required for the encoding/consolidation of overlapping memories. In this study, we provide evidence that consolidation of these “pattern-separated” memories requires the action of BDNF on immature neurons specifically.